INFLUENCE OF STREAM SPEED AND ELECTRICAL FORCE ON FILTRATION EFFICIENCY OF ULTRA DISPERSE AEROSOLS - M. V. Tumilovich; L. P. Pilinevich; А. E. Galkin (Наука и техника)
Main process regularities of the air cleaning from ultra disperse aerosols under the influence of electric forces at various flow velocities are theoretically and experimentally investigated in the paper. The paper demonstrates the fact that the filtration efficiency of particles having size of more than 1 micron is higher due to an increase of an inertial mechanism of particle deposition on the front fibers and partially on their back side and in the case of electric force action – on their back side. The filtration efficiency of particles having size of less than 1 micron is higher due to an increase of filtration velocity when particles and fibers are electrically charged.